Separating and Merging Cash Flows: Investigating Five-element Cash Flows Statement - Golestani, Hojatollah Atashi; Hosseini, Seyyed Mohammad; Mehrjoo, Ehsan (International Journal of Economics and Financial Issues, 2017)
In Iranian Accounting Standard, cash flows statement includes five elements. This is justifiable considering all discussions that exist in International Accounting Standard No.7 (IAS 7). This new representation method has raised many debates on its usefulness. In this study, cash flows from operations (CFO) were separated into different elements and the predictability of future earnings was examined by them as the most important criterion which would facilitate the evaluation of the performance along with net earnings. Using data of listed companies in Tehran Stock Exchange, results of testing research hypotheses showed that when a model including the elements of accruals and net CFO based on the IAS was used for predicting net earnings, separating CFO elements, disclosed by the direct method of representing cash flow statement and replacing these elements in the model did not increase the predictability of the model significantly. Also, the method of separating CFO into its gross sums based on IAS 7 had more predictability compared to the method of separating the items of cash flows into three (operating activities, return on investment and paid earnings for financing, and tax) elements according to Iranian Accounting Standard. Our results are applicable for the standard-makers and users of financial statements, developing disclosure literature in the financial statements. Keyword: Operating Cash Flows, Accruals, Predictive Ability, Accounting Standards. JEL Classifications: M41, G17